A Multidimensional Descriptive Analysis of Pulmonary Fibrosis: Clinical Profiles, Risk Factors, and Functional Impacts in Affected Patients - Asma Saleh Basos; Rabea Ali Ibrahim Abdulsamad (Journal of Libyan Academy Bani Walid, 2025)
Pulmonary fibrosis is a progressive chronic lung disease characterized by the scarring and stiffening of lung tissues, leading to impaired gas exchange and gradual respiratory failure. This study aimed to analyze the demographic and physiological characteristics of patients with pulmonary fibrosis, identify key contributing factors such as smoking, occupational exposure, and genetic history, and assess the disease’s impact on daily activities and quality of life. A total of 70 patients were included in the sample, and data were collected using a comprehensive questionnaire and statistically analyzed. The results showed that most participants were males and belonged to the older age group (60–79 years), with a mean oxygen saturation (SpO₂) of 59.16%, which is significantly lower than normal. A strong correlation was found between pulmonary fibrosis and a history of smoking, as well as occupational exposure to harmful substances such as bird proteins and volatile chemicals. Physical activity and the ability to work were the most affected aspects of daily life. The study recommends early screening programs, increased awareness of smoking risks and occupational hazards, and improved access to treatment and psychosocial support for patients.